Outpatient management of heart valve disease following the COVID-19 pandemic: implications for present and future care. Issue 20 (31st August 2020) - Shah, Benoy Nalin; Schlosshan, Dominik; McConkey, Hannah Zelie Ruth; Buch, Mamta Heena; Marshall, Andrew John; Cartwright, Neil; Dobson, Laura Elizabeth; Allen, Christopher; Campbell, Brian; Khan, Patricia; Savill, Peter John; Briffa, Norman Paul; et al.
Abstract : The established processes for ensuring safe outpatient surveillance of patients with known heart valve disease (HVD), echocardiography for patients referred with new murmurs and timely delivery of surgical or transcatheter treatment for patients with severe disease have all been significantly impacted by the novel coronavirus pandemic. This has created a large backlog of work and upstaging of disease with consequent increases in risk and cost of treatment and potential for worse long-term outcomes. As countries emerge from lockdown but with COVID-19 endemic in society, precautions remain that restrict 'normal' practice. In this article, we propose a methodology for restructuring services for patients with HVD and provide recommendations pertaining to frequency of follow-up and use of echocardiography at present. It will be almost impossible to practice exactly as we did prior to the pandemic; thus, it is essential to prioritise patients with the greatest clinical need, such as those with symptomatic severe HVD. Local procedural waiting times will need to be considered, in addition to usual clinical characteristics in determining whether patients requiring intervention would be better suited having surgical or transcatheter treatment. We present guidance on the identification of stable patients with HVD that could have follow-up deferred safely and suggest certain patients that could be discharged from follow-up if waiting lists are triaged with appropriate clinical input. Finally, we propose that novel models of working enforced by the pandemic—such as increased use of virtual clinics—should be further developed and evaluated.